Partial schauder estimates for a sub-elliptic equation - Wei, N.; Jiang, Yongsheng; Wu, Yong Hong (Elsevier BV, 2016)
In this paper, we establish the partial Schauder estimates for the Kohn Laplace equation in the Heisenberg group based on the mean value theorem, the Taylor formula and a priori estimates for the derivatives of the Newton potential.